(3fRgI GdCNHGQ aj eMGSf GdCNjGQs - (3eMeO Hf MSf Hf Ydj Hf YKeGf GdfhGLj GdTGaYj , TeS GdOjf,J (B859 (3g` s
(3ChdgG (B:s
(3hHYO , aEf eWGdYI GdJhGQjN hGdSjQ Yf dEfSGf Gdgehe hbO ChQOJ aj gPG GdcJGH eG MSf EjQGOg ef eMGSf Phi GdCdHGH MSHeG hbY Ydjg ENJjGQj s
(3BNQgG (B:s
(3GdThjfR ajg ZPGA cGdaVI GdHjVGA PgHkG eG bhjJ HGdfGQ Ydjg Jdai ai s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B88 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B203 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B200s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B57 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B446 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs